A mouse model with age-dependent immune response and immune-tolerance for HBV infection. Issue 6 (1st February 2018) - Yi, Xuerui; Yuan, Youcheng; Li, Na; Yi, Lu; Wang, Cuiling; Qi, Ying; Gong, Liang; Liu, Guangze; Kong, Xiangping
Highlights: Age-dependent HBV infection mouse model was setup in BALB/c background HBVRag1 mice. Reconstituted adult mice generated HBsAb, and higher number of CD8T and B cells with HBsAg clearance. A higher Th1/Th2 cytokine level in reconstituted young mice may benefit HBsAg persistent. The age-related tolerance was different from that noted in HBV-Tg mice that were sensitive to ampicillin. GS-9620 could inhibit HBsAg, while HBV vaccine achieved limited clearance of HBsAg. Abstract: Background: Viral clearance of human HBV infection largely depends on the age of exposure. Thus, a mouse model with age-dependent immune response and immune-tolerance for HBV infection was established. Methods: HBVRag1 mice were generated by crossing Rag1 −/− mice with HBV-Tg mice. Following adoptive transfer of splenocytes adult (8–9 weeks old) and young (3 weeks old) HBVRag1 mice were named as HBVRag-ReA and HBVRag-ReY mice respectively. The biochemical parameters that were associated with viral load and immune function, as well as the histological evaluation of the liver tissues between the two mouse models were detected. The immune tolerance of HBVRag-ReY mice that were reconstituted at the early stages of life was evaluated by quantitative hepatitis B core antibody assay, adoptive transfer, and modulation of gut microbiota with the addition of antibiotics. Results: HBVRag-ReA mice indicated apparent hepatocytes damage, clearance of HBsAg and production of HBsAb and HBcAb. HBVRag-ReY mice did not develop ALT elevation, and produced HBcAb and HBsAg. A higher number of hepatic CD8 + T and B cells promoted clearance of HBsAg in HBVRag-ReA mice following 30 days of lymphocyte transfer. In contrast to HBVRag-ReA mice, HBVRag-ReY mice exhibited higher levels of Th1/Th2 cytokines. HBVRag-ReY mice exhibited significantly higher ( P  < .01, approximately 10-fold) serum quantitative anti-HBc levels than HBV-Tg mice, which might be similar to the phase of immune clearance and immune tolerance in human HBV infection. Furthermore, the age-related tolerance in HBVRag-ReY mice that were sensitive to antibiotic treatment was different from that noted in HBV-Tg mice. GS-9620 could inhibit the production of HBsAg, whereas HBV vaccination could induce sustained seroconversion in HBVRag-ReY mice with low levels of HBsAg. Conclusions: The present study described a mouse model with age-dependent immunity and immune-tolerance for HBV infection in vivo, which may mimic chronic HBV infection in humans.